PERANAN MOTIVASI DALAM KERAJINAN BELAJAR SISWA - abd aziz; Mohamad Aso Samsudin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The one of the problems in the learning process is low spirit of students. It is often faced and experienced by teachers by almost all teachers in learning processes. The bad consequences of student’s low spirit in learning process are the learning outcomes did not reach the minimum criteria set by teacher. Various efforts need to be done by teachers to overcome and anticipate that problem. Teachers need to re-understand the techniques for motivating students and applying them in learning process. Theoretically, the students’ motivation can generate their own spirit in learning, both of motivation from outside and inside. To generate student’s motivation, teachers need to pay attention to the supporting factors. Teachers need to maximize these factors in running the learning process, so gradually students will be motivated to learn.